(untitled) (Global Journal of Science Frontier Research, 2017)
In spite of accurate predictions and an impressive explanation on perihelion of Mercury, Einstein’s general relativity accepted by the APS is currently infested with unsolved problems due to his own earlier errors together with additional errors from his followers. Although subsequently his linearized equation has provided more impressive results, Einstein was puzzled because his equation has no wave solutions, but his linearized equation has. The root is due to his accumulated inadequate proposals in physics, and inadequacy in pure mathematics of many physicists such as Pauli. Moreover, the contributions from mathematicians such as Penrose and Yau made the situation worse because they use invalid assumptions due to not understanding physics. These errors are responsible for the lack of progress in gravitation of the APS. Currently, there are ten major errors: 1) misinterpretation of the equivalence principle and the invalid covariance principle; 2) the conflict between the Einstein equation and E = mc2; 3) inadequacy of Einstein’s notion of photons and invalidity of E = mc2; 4) the invalid Space time Singularity Theorems of Hawking & Penrose; 5) the nonexistence of a dynamic solution and the Principle of Causality; 6) the rejection of the anti-gravitational coupling; 7) the absence of the reaction force for gravitational radiation; 8) the existence of repulsive gravitation; 9) the weight reduction of a charged capacitor and the current-mass interaction; 10) the necessary extension of general relativity to a five-dimensional space. A main problem is that physicists are incompetent in pure mathematics. This results in awarding the 2016 APS Medal for Exceptional Achievement in Research to Witten even without the support of experiments. There are three types of experiments that show formula E = mc2 is invalid, but the APS still did not recognize them because of the incompetence of Dr. Eric J. Weinberg, Editor of the Physical Review D, in mathematics and physics. Moreov